A Framework of Metacognitive Scaffolding in Learning Authoring System Through Facebook. (September 2016) - Jumaat, Nurul Farhana; Tasir, Zaidatun
Scaffolding refers to a guidance that helps students during their learning sessions whereby it makes learning easier for them. This study aims to develop a framework of metacognitive scaffolding (MS) to guide students in learning Authoring System through Facebook. Thirty-seven master degree students who were enrolled in Authoring System course from three different cohorts of study were selected as respondents. The study identified the dominant mechanism of MS prompted by the instructor, along with the dominant types of online interaction triggered by the students in a Facebook discussion. The data were analyzed by using content analysis technique. Data were collected from the observation through Facebook discussions. Results indicate that the dominant mechanisms of MS prompted by the instructors include guiding the students to focus on their learning processes, providing the students with an instant feedback, and also asking or presenting the rationale of the tasks and activities involved. The dominant types of online interactions include acknowledgment of opinion, evaluating own or other's understanding, and clarifying and elaborating own understanding. Based on these findings, the proposed framework recommends a series of rules that serves as a guideline for the instructor to produce meaningful learning among the students through MS.